(untitled) (Medico Legal Update, 2021)
Suicide is an important mental health problem in our society, as it is in most of the world’s developed nations. It’s an affliction that robs us of some of our community’s most active leaders. It is a most troubling type of mental disease to imagine, a mental disorder in which the victim’s pain and fear causes him to prefer death to his misery. Suicide is widespread. Most communities have earlier treated suicide as a felony and have instituted laws to restrict the act and prosecute those who attempt it whereas the notion have changed and now individuals who try or commit suicide are frequently viewed as depressed or mentally unstable. This Covid(Corona virus) pandemic had made the situation worse because many people are taking help from professionals for the first time due to severe increase of anxiety and stress. During this lockdown period many have developed suicidal tendencies and seeking physicians’ help. After the suicide of famous bollywood actor Sushant Singh Rajput many are talking about the mental health awareness. In this present paper we will analyze the problem of suicide, mental health care laws and suicide regulation and some strategies for suicide prevention.